Three new species of Carlosrosaea (Trimorphomycetaceae, Tremellales) from China - Wan-Li Gao; Chun-Yue Chai; Qiu-Hong Niu; Feng-Li Hui (MycoKeys)
Carlosrosaea is a genus of plant-associated yeasts within the family Trimorphomycetaceae of the order Tremellales. Currently, eight species have been described and accepted as members of the genus Carlosrosaea. In this study, six Carlosrosaea strains were isolated from the surface of leaves of the genera Camellia, Distylium, Glechoma, and Glochidion, collected in Fujian, Guizhou, Hainan, and Henan provinces. Based on phylogenetic analyses and phenotypic characterization, these strains were identified as three new Carlosrosaea species: C. camelliae sp. nov. (holotype CICC 33566T), C. glechomae sp. nov. (holotype CICC 33632T), and C. wuzhiensis sp. nov. (holotype GDMCC 2.526T). Descriptions, illustrations, and phylogenetic data of these new taxa are provided. This study enhances knowledge of Carlosrosaea species diversity in China and provides a foundation for future taxonomic and ecological research.